2008
DOI: 10.1590/s1516-89132008000500004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt and osmotic stresses on the germination of pepper seeds of different maturation stages

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 21 publications
3
24
0
5
Order By: Relevance
“…Similarly, Duman [23] and Yıldırım et al [24] determined that PEG, KNO 3 and NaCl treatments had significantly increased on germination percentage of onion seeds compared that of the control. Demir and Mavi [25] reported that the pepper seed germination was higher and sensivity index were lower in NaCl than in PEG treatments in both water potential and harvest. In the another research, they reported that the salt priming (KNO 3 , 3%, 6 day, 20°C) increased watermelon emergence and produce well-developed seedlings particularly in early spring sowings at low temperatures in greenhouse conditions [26].…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Duman [23] and Yıldırım et al [24] determined that PEG, KNO 3 and NaCl treatments had significantly increased on germination percentage of onion seeds compared that of the control. Demir and Mavi [25] reported that the pepper seed germination was higher and sensivity index were lower in NaCl than in PEG treatments in both water potential and harvest. In the another research, they reported that the salt priming (KNO 3 , 3%, 6 day, 20°C) increased watermelon emergence and produce well-developed seedlings particularly in early spring sowings at low temperatures in greenhouse conditions [26].…”
Section: Discussionmentioning
confidence: 98%
“…Germination was carried out in a growth chamber under a 12/12 h photoperiod (light/darkness), light intensity of 180 μmol m -2 s -1 and temperature of 25 ºC, for 12 days. Thiram was added to the solutions at a concentration of 0.2 % (v/v) to control the fungi infection (Demir & Mavi 2008). Seeds were considered germinated when the primary root was longer than 5.0 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Salinity affects the dry and fresh mass (Tabatabaei 2006;Blanco et al 2008;Demir and Mazi 2008) the development and the productivity of cultivated species (Neto and Nogueira 1999;Kaya et al 2007;Zheng et al 2008;Demiral 2009, Galvan-Ampudia andTesterink 2011). Reduction in the growth rate of the leaf can represent an adaptation to salt stress, since increased levels of salts in the soil impedes the uptake of water by the plant (Carillo et al 2005) and the reduction in leaf area limits transpiration (Neumann 1997).…”
Section: Introductionmentioning
confidence: 99%